2023
DOI: 10.3390/su152416860
|View full text |Cite
|
Sign up to set email alerts
|

A Streamline Sustainable Business Performance Reporting Model by an Integrated FinESG Approach

Victoria Bogdan,
Luminita Rus,
Dana Simona Gherai
et al.

Abstract: ESG reporting and disclosure enable financial performance by attracting revenues and optimizing managerial decisions. Within this landscape falls the present study that aimed to examine the quality of ESG reporting connected to the financial performance of listed companies. Stratified analysis revealed four groups of companies according to the average value of ROA and ROE indicators, as well as four classes according to the average ESG disclosure score. The analysis of GRI topics and materiality disclosure sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…This research explores artificial intelligence's impact on improving the audit process's effectiveness and quality. The results indicate that when auditing firms, huge ones will continue to invest in specialized expert systems and neural networks tailored to the industry and specific audit tasks to minimize their audit risks (Bogdan et al 2023). Additionally, large multinational corporations may develop their internal auditing functions to employ such systems to reinforce internal control systems and reduce business risks.…”
Section: Ai In the Audit Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…This research explores artificial intelligence's impact on improving the audit process's effectiveness and quality. The results indicate that when auditing firms, huge ones will continue to invest in specialized expert systems and neural networks tailored to the industry and specific audit tasks to minimize their audit risks (Bogdan et al 2023). Additionally, large multinational corporations may develop their internal auditing functions to employ such systems to reinforce internal control systems and reduce business risks.…”
Section: Ai In the Audit Fieldmentioning
confidence: 99%
“…The TRAM, proposed by Bogdan et al (2023), aims to enhance both TR and TAM's applicability and explanatory power. The suggested model supplements TAM's two specific dimensions (PEOU and PU) with TR's personality dimensions (Firoiu et al 2023b).…”
Section: Technology Readiness and Acceptance Model (Tram)mentioning
confidence: 99%
See 1 more Smart Citation
“…ESG activities are rooted in corporate business operations and are closely related to financial performance [95]. Studies also show that corporate social responsibility (CSR) activities, which serve as a standard for evaluating corporate value and sustainability, are determinants of financial performance [96][97][98]. Khan et al (2023) [99] showed that community-oriented CSR activities and environmental protection-focused CSR activities improve the sustainability of SMEs.…”
Section: Esg Managementmentioning
confidence: 99%
“…According to the research conducted by (Anh et al 2024), the sustainability report is a valuable information channel for enterprises and stakeholders about three essential aspects of a company: economy, society, and environment. In addition, relating to the research of Bogdan et al (2023), sustainability reports are designed to systematize and disseminate quantitative and qualitative information on sustainable business issues, encouraging engagement and providing transparency to all stakeholders (Khémiri et al 2024;Khezri et al 2024;Lee and Kim 2024).…”
Section: The Definition Of Sustainability Reportmentioning
confidence: 99%